The politics of the Kiobel decision: The United States Supreme Court narrowing of jurisdiction under the Alien Tort Statute - McNally, Claire (AUC Knowledge Fountain, 2018)
This thesis examines the United States’ Supreme Court’s decision in the Kiobel case and argues the decision unjustly and unreasonably favored the interests of corporations over human rights. In doing so, the Court significantly narrowed the scope of the Alien Tort Statute in a manner which allowed the Court to distance itself from and obscure the inescapable political costs of the Kiobel decision. The Court does so by focusing on technical jurisdictional questions instead of the thorny issue of corporate responsibility for human rights abuses committed or encouraged in the pursuit of profit. Even on the jurisdictional and technical legal questions, the Court is selective, inconsistent, and contradictory in how it applies legal reasoning. This thesis analyzes both the Court’s legal inconsistencies and the politics of its decision. In the early twenty-first century, plaintiffs successfully established jurisdiction under the Alien Tort Statute in the U.S. federal court system and won damages against corporations for extraterritorial human rights abuses. The Kiobel plaintiffs, former residents of the Ogoniland region of Nigeria, filed a case against the Royal Dutch Petroleum Company and the U.K.’s Shell Trade and Transportation Company for aiding and abetting human rights violations and environmental destruction committed by the Nigerian government. I begin by discussing the evolution of Alien Tort jurisprudence in the U.S. and the facts of the Kiobel case. Then, I assemble my conceptual framework drawing on the relationship between law and politics, specifically as it plays out in international law. Next, I explain the Court’s decision in Kiobel. I demonstrate the legal inconsistencies in the decision, followed by a discussion of the larger political issues impacting the decision. I chose this structure not because I view the legal and political questions as distinct, but because I believe this structure best highlights the impact of the unspoken political considerations on the legal decisions made in Kiobel.